2014
DOI: 10.6004/jnccn.2014.0099
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer, Version 3.2014

Abstract: OverviewColorectal cancer (CRC) is the fourth most frequently diagnosed cancer and the second leading cause of cancer death in the United States. In 2013, an estimated 102,480 new cases of colon cancer and approximately 40,340 cases of rectal cancer will occur. During the same year, an estimated 50,830 people will die of colon and rectal cancers combined. AbstractThe NCCN Guidelines for Colon Cancer address diagnosis, pathologic staging, surgical management, perioperative treatment, posttreatment surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
177
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 130 publications
(191 reference statements)
3
177
0
Order By: Relevance
“…Although, screening programs for CRC are widely used in western countries (Benson et al, 2008;Ng and Wong 2013;Benson et al, 2014), there currently does not exist recognized cancer screening programs in the Middle Eastern or: such as Iran. After a thorough study of the literature, it was noted that there have not been research efforts with regards to CRC screening among the average risk population in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Although, screening programs for CRC are widely used in western countries (Benson et al, 2008;Ng and Wong 2013;Benson et al, 2014), there currently does not exist recognized cancer screening programs in the Middle Eastern or: such as Iran. After a thorough study of the literature, it was noted that there have not been research efforts with regards to CRC screening among the average risk population in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a population-based epidemiological study in a Chinese population found that the NK2R rs4644560 genotype appeared to be associated with a decreased risk of CRC when combined with NK1R rs10198644 (12 An individual who consumed alcohol more than once per day for at least three months was considered as an alcohol drinker and an individual who had smoked more than one cigarette per day for over one year was considered as a tobacco user. Diagnostic stage was confirmed according to the National Comprehensive Cancer Network guidelines for CRC (13). Differentiation grade was defined as poor, moderate and well.…”
Section: Introductionmentioning
confidence: 99%
“…(J Mol Diagn 2016, 18: 299e315; http:// dx.doi.org/10.1016/j.jmoldx. 2015.11.006) In modern oncologic practice, patients with advanced-stage non-small cell lung cancer (NSCLC), 1,2 melanoma, 3,4 and colorectal adenocarcinoma 5,6 are often treated with targeted therapies as standard of care or after enrollment in clinical trials. Molecular mutation analysis is the preferred testing modality to guide therapeutic decision making and/or eligibility for biological studies.…”
mentioning
confidence: 99%